2015
DOI: 10.1038/hr.2015.64
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial comparing the velocities of the antihypertensive effects on home blood pressure of candesartan and candesartan with hydrochlorothiazide

Abstract: We aimed to evaluate the hypotensive effect and the time to attain the maximal antihypertensive effect (stabilization time) of 8 mg candesartan/6.25 mg hydrochlorothiazide (HCTZ) combination therapy (combination regimen) and therapy with an increased candesartan dose (12 mg; maximum dose regimen) using home blood pressure (BP) measurements. A prospective, multicenter, open-label, randomized, comparative trial was conducted. Essential hypertensive patients who failed to achieve adequate BP control (systolic BP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Even in the present clinical trial, although all participants were available to measure their nocturnal home BP on the first night, they were not able to continue the measurements for the seven consecutive nights of either phase of the protocol. In a previous study, one of the main purposes of which was to assess the changes in nocturnal home BP over three nights following an antihypertensive medication, only 26% of the 206 participants successfully measured their nocturnal home BP on all three nights . On the other hand, since there has been much evidence that nocturnal BP is a better predictor of future cardiovascular events than daytime BP, we concluded that nocturnal BP should be measured in clinical practices, and thus it is important to measure nocturnal home BP values over the long term under standard conditions.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Even in the present clinical trial, although all participants were available to measure their nocturnal home BP on the first night, they were not able to continue the measurements for the seven consecutive nights of either phase of the protocol. In a previous study, one of the main purposes of which was to assess the changes in nocturnal home BP over three nights following an antihypertensive medication, only 26% of the 206 participants successfully measured their nocturnal home BP on all three nights . On the other hand, since there has been much evidence that nocturnal BP is a better predictor of future cardiovascular events than daytime BP, we concluded that nocturnal BP should be measured in clinical practices, and thus it is important to measure nocturnal home BP values over the long term under standard conditions.…”
Section: Discussionmentioning
confidence: 88%
“…On the other hand, participants are likely to measure nocturnal BP levels depending on their own lifestyle. Recently developed HBPM devices permit participants to set specific lengths of time after their chosen bedtime for the measurement of nocturnal BPs . Although there may be differences between the nocturnal BP values measured at intervals after a participant‐specified bedtime and those measured at fixed time points, the previous studies on nocturnal HBPM have not taken such measurement conditions into consideration .…”
Section: Introductionmentioning
confidence: 99%